Fit2Ear: Generating Personalized Earplugs from Smartphone Depth Camera Images - Zhao, Haibin; Röddiger, Tobias; Feng, Yufei; Beigl, Michael (UbiComp '24: Companion of the 2024 on ACM International Joint Conference on Pervasive and Ubiquitous Computing, 2024)
Earphones, due to their deep integration into daily life, have been developed for unobtrusive and ubiquitous health monitoring. However, these advanced algorithms greatly rely on the high quality sensing data. However, the data collected with universal earplugs could potentially generate undesirable noise, such as vibrations or even falling off. As a result, the algorithms may exhibit limited performance. In this regard, we build a dataset containing RGBD and IMU data captured by a smartphone. To provide a precise and solid ground truth, we employ additional control information from a robotic arm that holds the smartphone scanning ears along a predefined trajectory. With this dataset, we propose a tightly coupled information fusion algorithm for the ground truth ear modeling. Finally, we fabricate the earplugs and conduct an end-to-end evaluation of the wearability of the modeled earplugs in a user study.
CRIS-Team Scopus Importer:2025-02-04
Keywords: 3D modeling; customization; earable; earplug; sensor fusion

Squeezing the Threshold of Metal-Halide Perovskite Micro-Crystal Lasers Grown by Solution Epitaxy - Zhou, Shuyu; Rehm, Viktor; Afify, Hany A.; Feng, Yufei; Korczak, Jędrzej; Szczerbakow, Andrzej; Story, Tomasz; Peng, Zijian; These, Albert; Barabash, Anastasia; Osvet, Andres; Brabec, Christoph; et al. (Advanced Functional Materials, 2024)
Metal halide perovskite semiconductors have demonstrated remarkable progress not only in photovoltaics and X-ray detection but also in laser technologies. Particularly appealing is the simplicity with which micro-crystallites can be epitaxially grown, thereby forming micro-resonators suitable for lasing. Here, the laser threshold is optimized by selecting excitation laser parameters and by improving material quality. The latter process is conducted for formamidinium lead tribromide, emitting in the green spectral range. Depending on the growth method and parameters, the sizes of the micro-resonators can be tuned between ≈3 and 23 micrometers. Under laser excitation systematically lower thresholds are observed for micro-resonators in the 4–7 micrometer size range, than for larger ones, irrespective of growth method. Among three optimized growth methods, epitaxial growth via antisolvent vapor-assisted crystallization exhibits the smallest threshold powers, indicating the highest material quality. This conclusion is supported by hyperspectral microscopic luminescence imaging and by transient photoluminescence. The best laser structures exhibit record threshold powers for epitaxially grown perovskites, indicating that the selected antisolvent vapor epitaxial growth holds great promises also for other perovskite materials.
CRIS-Team Scopus Importer:2024-05-10
Keywords: FAPbBr; lasing; micro-resonators; perovskites; solution epitaxy